Causes of Pathological Vaginal Discharge and Impacts on Adolescent Reproductive Health - Salina, Salina; Arlina, Andi; Purnamasari, Dian (Advances in Healthcare Research, 2025)
Purpose: This study aims to identify and analyze in depth various factors causing pathological vaginal discharge in adolescent girls and evaluate its implications for reproductive health. The primary focus is on the interaction between biological aspects, personal hygiene behavior, social and cultural constructs, and access to health information and services. Research Method: This study employs a qualitative approach, utilizing a systematic literature review of national and international scientific articles published between 2020 and 2025. The analysis is conducted thematically to group the causal factors and analyze their interrelationships based on reliable academic references. Results and Discussion: Findings indicate that pathological vaginal discharge in adolescents is caused by a combination of hormonal changes, vaginal microflora imbalance, and poor hygiene practices, such as wearing tight pants and improper cleaning of the genital area. Cultural norms that taboo discussions about reproductive health further exacerbate delays in treatment. The lack of formal sexual education and access to youth-friendly health services are significant barriers to the prevention and management of vaginal discharge. Implications: This study emphasizes the importance of a holistic, intersectoral, and sustainable educational approach. Single interventions are insufficient to address this issue. Recommendations are directed toward integrating reproductive education into school curricula and providing inclusive and accessible adolescent health services.